Relations Between Modality, Evidentiality and Illocutionary Force - Ницолова, Руселина (Języki słowiańskie dziś: w kręgu kategorii, struktur i procesów, 2021)
This article deals with the relationship between modality, evidentiality, admirativity and illocutionary force in Bulgarian. Like DeLancey (DeLancey, 2001), we believe that modality, evidentiality and admirativity encodе various types of information about information. The study examines the effect of evidentiality in sentences with different illocutionary force: declaratives, interrogatives, imperatives, optatives and permissives.